Oxyntic gastric atrophy in Helicobacter pylori gastritis is distinct from autoimmune gastritis - Venerito, Marino; Varbanova, Mariya; Röhl, Friedrich Wilhelm; Reinhold, Dirk; Frauenschläger, Katrin; Jechorek, Doerthe; Weigt, Jochen; Link, Alexander; Malfertheiner, Peter (Journal of Clinical Pathology, 2016)
Aim To assess characteristics of oxyntic gastric atrophy (OGA) in autoimmune gastritis (AIG) compared with OGA as a consequence of Helicobacter pylori infection. Methods Patients undergoing oesophagogastroduodenoscopy from July 2011 to October 2014 were prospectively included (N=452). Gastric biopsies were obtained for histology and H. pylori testing. Serum gastrin-17 (G17), pepsinogen (PG) I, PGII and antibodies against H. pylori and cytotoxin-Associated gene A protein were determined in all patients. Antibodies against parietal cells and intrinsic factor were determined in patients with advanced (moderate to severe) OGA. Areas under the receiver operating characteristic curves (AUCs) were calculated for serum biomarkers and compared with histology. Results Overall, 34 patients (8.9%) had advanced OGA by histology (22 women, age 61±15 years). Current or past H. pylori infection and AIG were present in 14/34 and 22/34 patients, respectively. H. pylori-negative AIG patients (N=18) were more likely to have another autoimmune disease (OR 6.3; 95% CI 1.3 to 29.8), severe corpus atrophy (OR 10.1; 95% CI 1.9 to 54.1) and corpus intestinal metaplasia (OR 26.9; 95% CI 5.3 to 136.5) compared with H. pylori-positive patients with advanced OGA. Antrum atrophy was present in 39% of H. pylori-negative AIG patients. The diagnostic performance of G17, PG I and PGI/II was excellent for AIG patients (AUC=0.83, 0.95 and 0.97, respectively), but limited for H. pylori-positive patients with advanced OGA (AUC=0.62, 0.75 and 0.67, respectively). Conclusions H. pylori-negative AIG has a distinct clinical, morphological and serological phenotype compared with advanced OGA in H. pylori gastritis.
CRIS-Team Scopus Importer:2025-10-13